Modulation of behavior before COVID-19, in contact patients treated at the Villa Azucarera isolation center - Isela Casas Olazabal; Enia Lorenzo Pérez; Maria Cristina Pérez Guerrero; Jaqueline García Rodríguez; Ricardo Vázquez Casas (Medisur)
Background: The prevention of the contagion of the SARS-CoV-2 coronavirus is the main weapon against the disease, and in Cuba it is carried out, fundamentally, with social isolation in specific centers where a modeling of the behavior of classified people is intended as contacts. Objective: To describe the modulation of behavior in contact patients treated in the Villa Azucarera isolation center before, during and at the end of their epidemiological surveillance. Methods: Observational, descriptive and cross-sectional study in the Villa Azucarera de Camagüey isolation center for patient contacts of SARS-CoV-2 coronavirus patients during February and March 2021. Theoretical methods were used: analysis-synthesis and inductive-deductive and empirical: observation, epidemiological survey and interviews. Results: Behavior modulation was demonstrated at the conclusion of the epidemiological surveillance and the increase in the need to use the nasobuco, frequent hand washing and social distancing. Male patients aged between 31 and 40 years predominated. Conclusions: The attitude of the patient during the surveillance in the institution changes from an explicit rejection at the beginning, to an acceptance at the time of discharge, and an increase in the perception of the risk of becoming ill due to the increase in the level of information and of the therapeutic relationship established with health personnel.